THE PROBLEM OF ARITY IN STOIC LOGIC: THE CASE OF THE DISJUNCTION - López-Astorga, Miguel (THÉMATA. Revista de Filosofía, 2016)
Both ancient sources and contemporary authors seem to agree, in general, that the Stoic disjunction was exclusive. The problem is that some ancient sources inform that the Stoics also considered disjunctions with more than two disjuncts and stated that such disjunctions were true if only one of their disjuncts was true as well. This appears to be a logical mistake, since an exclusive disjunction with three disjuncts can be true if its three disjuncts are true too. However, in this paper, I analyze this problem based on the mental models theory, and try to show that, under criteria different from those of standard logic, it is possible to claim that, in an exclusive disjunction with more than two disjuncts, only one disjunct can be true